Epigrammatic status and perspective of sequestration of carbon dioxide: Role of TiO2 as photocatalyst. (1st January 2018) - Kumar, Sanjeev; Jain, Sapna; Yadav Lamba, Bhawna; Kumar, Pankaj
Abstract: Owing to tremendous increasing Carbon dioxide emissions, the environment and our lives have been affected by global warming and climate changes. There is a growing need to mitigate CO2 emissions. Some of the strategies to mitigate CO2 emissions are energy conservation, carbon capture and storage and using CO2 as a raw material in chemical processes. One of the best routes to remedy CO2 is to transform it to hydrocarbons via photo reduction. The paper presents the trends on the different methods of conversion of carbon dioxide into hydrocarbons. Among various methods, use of photo catalyst TiO2 is widely studied due to its comparatively low cost, low toxicity and its ability to resist photo corrosion. The importance of titania correlating with its properties is presented. Different doping of TiO2 is mentioned. The review concluded that TiO2 represents an effective photo catalyst for conversion of carbon dioxide leading to purification of environment and solution to energy crisis.